Experimental study on flow characteristics and heat transfer of an oscillating jet in a cross flow. (July 2021) - Mohammadshahi, Shabnam; Samsam-Khayani, Hadi; Cai, Tao; Nili-Ahmadabadi, Mahdi; Kim, Kyung Chun
Highlights: The trajectory of the OJICF is shallower than the JICF's. OJIF should be applied for film cooling rather than impinging applications. Heat transfer of IJICF is dominated by the impinging jet. Heat transfer of IOJICF is dominated by the cross flow. Heat transfer performance of the IJICF is superior to that of the IOJICF. Abstract: In the present paper, flow characteristics of an oscillating jet in a cross-flow (OJICF) emitted from a double feedback fluidic oscillator were investigated. The results were compared with a steady jet in a cross-flow (JICF) from a jet nozzle with length and diameter equal to those of the fluidic oscillator. Smoke visualization in a low-speed wind tunnel was used. The measurements were done in the symmetry plane with 3 cross sections for 4 different blowing ratios (BR) of 1 to 3.33. The OJICF shows high potential to enhance the effectiveness of film cooling since it penetrates to a lesser height and leads to considerable spanwise penetration. Then, heat transfer behaviors of an impinging OJICF (IOJICF) and impinging JICF (IJICF) were compared via thermographic phosphor thermometry (TPT). The cross-flow Reynolds number based on the hydraulic diameter of the jet exit and cross-flow velocity was varied between 510 and 2, 700, and the spacing between the jet and target surface was 3 times the jet throat's hydraulic diameter. The results show that for the IOJICF, heat transfer is dominated by the cross flow, and changing the BR does not have a significant effect. However, the IJICF promotes heat transfer around 2 times more than the IOJICF, and the more the BR is, the greater the Nu number. Therefore, the OJICF could be applied for film cooling rather than impinging applications.